2022
DOI: 10.3389/fmed.2022.884608
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Anti-vascular Endothelial Growth Factor Injection for Retinopathy of Prematurity: A Systematic Review and Meta-Analysis

Abstract: BackgroundLaser photocoagulation and/or intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections constitute the current standard treatment for retinopathy of prematurity (ROP). This systematic review and meta-analysis aimed to assess the efficacy and safety of anti-VEGF monotherapy for ROP treatment using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach.MethodsWe searched the Medline, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…With respect to safety outcomes, some studies reported the potential risk of complications like retinal detachment, visual field loss, and cataracts after laser treatment [ 53 , 54 ]. A meta-analysis by Taher et al [ 55 ] suggested that anti-VEGF injections were associated with significantly fewer adverse events than laser in general. However, Popovic et al [ 52 ] found there was no significant difference between anti-VEGF and laser for all analyzed complications, including vitreous hemorrhage, retinal detachment, and retinal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to safety outcomes, some studies reported the potential risk of complications like retinal detachment, visual field loss, and cataracts after laser treatment [ 53 , 54 ]. A meta-analysis by Taher et al [ 55 ] suggested that anti-VEGF injections were associated with significantly fewer adverse events than laser in general. However, Popovic et al [ 52 ] found there was no significant difference between anti-VEGF and laser for all analyzed complications, including vitreous hemorrhage, retinal detachment, and retinal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the amount of VEGF in the vitreous body is high in ROP stage 4 [4]. Several studies reported good anatomical and visual outcomes for intravitreal anti-VEGFs in ROP stage 4 [4,5]. The conventional treatment for high-risk pre-threshold retinopathy of prematurity (ROP) involves traditional laser therapy targeting the non-vascularized retina, eliminating cells producing Vascular Endothelial Growth Factor (VEGF) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ophthalmic treatment includes laser photocoagulation for peripheral avascular retina and intravitreal anti-VEGF for neovascularization. 61 , 62 …”
Section: Introductionmentioning
confidence: 99%
“…Treatment focuses on symptom management and includes skin grafting, surgery to repair skin lesions and skull abnormalities, prostheses for limb malformations, laser photocoagulation to the avascular retina to arrest the potential evolution from ischemia to neovascularization, and intravitreal anti-VEGF for neovascularization. 62 , 66 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation